Chemical and physical properties of natural and modified ground peanut hulls - Truluck, Holly D. (2017)
The chemical and physical characteristics of peanut hulls was assessed using methylene blue (MB) adsorptivity, physical analysis to assess surface area, and FT-IR spectroscopy to analyze chemical composition of the hulls. Peanut hulls are an agriculture waste that show promise for cation adsorption due their lignocellulosic makeup. Adsorption is a process in which a thin layer of molecules adheres to a surface with which they come in contact. The ground peanut hulls are separated by density into two categories, high density (HD) and low density (LD). These two types of hulls react differently to an alkaline peroxide modification process, and therefore have different MB adsorption capacities. Unmodified HD hulls adsorb 0.08 +/- 0.05 mmol of MB per gram of hull and unmodified LD hulls adsorb 0.2 +/- 0.05 mmol of MB per gram of hull. Once modified, the adsorption capability increases depending on the modification procedure used. The chemical and physical characteristics of unmodified and modified ground peanut hulls were assessed to explain these differences. A 2-propanol displacement test showed that LD hulls have more empty space than HD hulls, which provides greater accessibility to adsorbates. Infrared spectroscopy showed the modifying alkaline solution dissolves lignin and other alkaline soluble hull components, which further increases the surface area of the hulls. The modification may also result in an increase of C=O functional groups, which would be strong binding sites for cations. It was determined that ground peanut hulls may be an appropriate biosorbent for cationic contaminants in low concentration, but a modification involving minimum concentrations of 0.45 M NaOH and 15% hydrogen peroxide is needed to raise the adsorption capacity of the hulls.